THE INFLUENCE OF WORK CLIMATE AND FATIGUE ON EMPLOYEE PERFORMANCE MEDAN SAMSAT WITH JOB SATISFACTION AS A MEDIATING VARIABLE IN NORTH MEDAN SAMSAT - Tri Amelia Risa; Wilchan Robain; M. Chaerul Rizky (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study focuses on analyzing job satisfaction in mediating work climate and burnout on employee performance. Aquantitative approach was chosen for this study, and the data source was obtained by distributing questionnaires to 74 employees at Samsat Medan Utara. Data analysis using Structural equation model (PLS-SEM). The results showed that in North Medan Samsat, the work environment directly impacts job satisfaction. At the North Medan Samsat, the work environment directly affects employee performance. Directly, burnout does not affect employee job satisfaction at the North Medan Samsat. Job satisfaction directly affects employee performance at the North Medan Samsat. Job satisfaction directly affects employee performance at the North Medan Samsat. At the North Medan Samsat, job satisfaction indirectly moderates the effect of work climate on employee performance. At the North Medan Samsat, job satisfaction does not significantly moderate the impact of burnout on employee performance.